2020
DOI: 10.24875/ric.19003215
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HLA-DPB1 Matching on Clinical Outcomes after Haploidentical-Related Hematopoietic Stem Cell Transplantation

Abstract: Background: The impact of HLA-DPB1 compatibility and its role as a transplantation antigen in haploidentical-related hematopoietic stem cell transplant (haplo-R-HSCT) have not been established, and a negative effect on survival has been suggested. Objective: The objective of the determine was to study the frequency and clinical effects of incompatibility at the HLA-DPB1 locus in the haplo-R-HSCT setting. Methods: Clinical records and electronic files of 91 patients with a hematological disease who underwent ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…The role of the HLA-DPB1 has gained greater relevance due to its association with various pathologies, including cancer ( 59 ), autoimmune diseases, such as rheumatoid arthritis ( 60 ), responses to viral infection ( 61 ), and vaccines ( 62 , 63 ). Regarding stem cell transplants, there is still controversy about the inclusion of the HLA-DPB1 locus in the search algorithms for 12/12 histocompatibility ( 64 ) due to the increasing number of reports indicating that a mismatch in this locus increases the risk of developing GVHD ( 65 ). Data for HLA-DPB1 and other HLA class II loci is reported for the first time in high-resolution in Colombia.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the HLA-DPB1 has gained greater relevance due to its association with various pathologies, including cancer ( 59 ), autoimmune diseases, such as rheumatoid arthritis ( 60 ), responses to viral infection ( 61 ), and vaccines ( 62 , 63 ). Regarding stem cell transplants, there is still controversy about the inclusion of the HLA-DPB1 locus in the search algorithms for 12/12 histocompatibility ( 64 ) due to the increasing number of reports indicating that a mismatch in this locus increases the risk of developing GVHD ( 65 ). Data for HLA-DPB1 and other HLA class II loci is reported for the first time in high-resolution in Colombia.…”
Section: Discussionmentioning
confidence: 99%
“…All haploidentical donors will be at least a 5/10 match to the patient. There are currently no data that suggest a different outcome for haploidentical donors who may have no sharing of DP type due to recombination, that is 5/12 v 6/12 (Jaime‐Pérez et al., 2020). Additional HLA matching on the mismatched haplotype may be observed; however, the EBMT consensus recommendation (Ciurea et al., 2020) concluded that there was no evidence to support a beneficial effect of selecting haploidentical donors based on the degree of additional HLA matching due to heterogeneity in data currently available.…”
Section: Histocompatibility Matching: Related Donor Selectionmentioning
confidence: 99%